Land use change analysis of Erdemli-Kız Kalesi region by using GIS methodology - Oral, Hasan Volkan. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2002., 2002)
According to scientific authorities in the year of 2025, the majority of the world's population around 5 billion people will be living in urban areas. As human settlements expand, prime agricultural land and habitats such as wetlands, forests, and watersheds are transformed into land for housing, roads and industry. In the developing countries the urban poor, searching an alternative place to live, often establish informal settlements in ecologically fragile areas.Changes in land-use and land cover have important consequences for natural resources through their impacts on soil and water quality, biodiversity, and global climatic systems. Land use and changes are particularly related to increase of population and intensive agriculture. With the awareness of the importance of land-use changes at coast sides, the study of regional or global land use change has become the focus of much scientific authorities and international organizations. From past to future remote sensing technology has been recognised as a useful means of supplying up to date information on activities within the urban environment . At the same time, computer based geographic information systems are being used to improve the management and use of information. The aim of the study is : to determine the land use changes through the years in the coast of Erdemli and Kizkalesi by using the Geographical Information System , ARC- VIEW GIS software and ER MAPPER .
Keywords: Land use -- Turkey.; Geographic information systems.; Urbanization -- Turkey.